COMPARATIVE ANALYSIS OF COMPETITION ANXIETY OF BOSNIAN AND HERZEGOVINIAN ATHLETES IN RELATION TO THE TYPE OF SPORT - Elvis Vardo; Damir Ahmić (Sport Scientific And Practical Aspects, 2025)
The concept of competition anxiety has been increasingly recognized as a basis for success in competitive sports. Therefore, we examined whether the type of sport the athletes train for is a distinguishing factor of the demonstrated level of competition anxiety. Using a sample of 38 athletes (26 basketball players and 12 cyclists) from four clubs in Bosnia and Herzegovina we tested forms of anxiety (cognitive and somatic anxiety) and the level of self-confidence just before the game (30 minutes before the game). Testing was conducted using the Competitive State Anxiety Inventory-2; CSAI-2, Martens et al., 1990, and the obtained results differ from the results in similar studies. For our sample, we can say that the basketball players show significantly higher levels of self-confidence, while the effects of competition anxiety are uniform in both groups of athletes.